An affair at Stonecliffe - Camp, Candace (Camp, Candace. Stonecliffe novel., 2022)
After hiding for five years from her late husband's family who wants to take her son, Gil, away from her, Noelle Rutherford must finally deal with the past when Carlisle Thorne catches up to her, saving them from someone after Gil's inheritance.